Use of Social Media for Marketing of Agricultural Products Among Agricultural Producers in Lakhimpur District in Assam: A Study - Saikia, Anjuma; Kumari, Deepika; Choudhary, Ranjeet Kumar (Journal of Agricultural Extension Management, 2021)
This study aims to know the use, purpose, importance, and problems the farmers face in marketing agricultural products through social media. For this study, 124 farmers are selected as the research sample. The findings of this paper showed that the most preferred social media among farmers are Youtube and WhatsApp. Samples under study use social media to promote agricultural products and share photos and videos relating to agricultural produces. A structured questionnaire was distributed to the respective farmers in the Lakhimpur district.